Survey on Secure Intrusion Detection and Countermeasures in Cloud - MM, Ankitha; Azath, M (International Journal of Computer Sciences and Engineering, 2014)
Cloud computing refers to both the application delivers services over the internet and the hardware and system software in the data centers that provide those services. Cloud is attracted by many users because of its security and storage features. The main attack faced by cloud is Distributed Denial of Services (DDOS), in which multiple hosts attack made simultaneously in all network. Security is an important issue in the cloud computing, but the problem is how effectively mitigating intruders and chooses correct counter measures. To counterattack insecure attacks from the virtual machines installed in the cloud proposing vulnerability detection, measurement, along with countermeasure mechanism known as NICE(Network Intrusion detection and Countermeasure Evaluation). In this survey aims to analyze intrusion detection and effective countermeasure mechanisms for achieving security on the virtual machines installed in cloud.